Trial to Encourage Adoption and Maintenance of a MEditerranean Diet (TEAM-MED): a randomised pilot trial of a peer support intervention for dietary behaviour change in adults from a Northern European population at high CVD risk. Issue 7 (14th October 2022) - McEvoy, Claire T.; Moore, Sarah; Erwin, Christina; Kontogianni, Meropi; Wallace, Sara Megan; Appleton, Katherine M.; Cupples, Margaret; Hunter, Steven; Kee, Frank; McCance, David R.; Patterson, Christopher C.; Young, Ian S.; et al.
Abstract: Adhering to a Mediterranean diet (MD) is associated with reduced CVD risk. This study aimed to explore methods of increasing MD adoption in a non-Mediterranean population at high risk of CVD, including assessing the feasibility of a developed peer support intervention. The Trial to Encourage Adoption and Maintenance of a MEditerranean Diet was a 12-month pilot parallel group RCT involving individuals aged ≥ 40 year, with low MD adherence, who were overweight, and had an estimated CVD risk ≥ 20 % over ten years. It explored three interventions, a peer support group, a dietician-led support group and a minimal support group to encourage dietary behaviour change and monitored variability in Mediterranean Diet Score (MDS) over time and between the intervention groups, alongside measurement of markers of nutritional status and cardiovascular risk. 118 individuals were assessed for eligibility, and 75 (64 %) were eligible. After 12 months, there was a retention rate of 69 % (peer support group 59 %; DSG 88 %; MSG 63 %). For all participants, increases in MDS were observed over 12 months ( P < 0·001), both in original MDS data and when imputed data were used. Improvements in BMI, HbA1c levels, systolic and diastolic blood pressure in the population as a whole. This pilot study has demonstrated that a non-Mediterranean adult population at high CVD risk can make dietary behaviour change over a 12-month period towards an MD. The study also highlights the feasibility of a peer support intervention to encourage MD behaviour change amongst this population group and will inform a definitive trial.